CMVL Sweet Corn 1: new high-yielding sweet corn - Khulbe, R K; Bisht, G S; Pant, M C (Indian Horticulture, 2019)
CMVL Sweet Corn 1 is a promising sweet corn hybrid on account of its high yield potential, desirable quality traits and disease tolerance. It is first public sector bred sweet corn hybrid released for wide cultivation under kharif rainfed conditions. Though a good number of sweet corn cultivars developed by private seed sector are also available, CMVLSC 1 offers farmers competitiveness in terms of seed price, which is important for extending the benefits of sweet corn cultivation to a wider section of the farming community.